Financial Behavior Sebagai Moderasi Pengaruh Financial Knowledge dan Financial Attitude Terhadap Financial Distress pada Generasi Milenial - Cicilia Erna Susilawati; Vania Dewi Sugiarto (J-MAS (Jurnal Manajemen dan Sains), 2021)
Millennials is very familiar with technology that makes it easier for them to access information and to do many things easily. However, this often makes the millennial generation less careful in managing finances, and causes financial problems. The study wanted to find out how the influence of financial knowledge and financial attitude on financial distress through financial behavior in the millennial generation. Data was collected using a questionnaire for millennial generation respondents who already have their own income. Data analysis using path analysis. The results show that financial knowledge does not directly affect financial distress, but financial knowledge has an effect on financial distress through financial behavior. This indicates that financial knowledge does not guarantee that millennials will avoid financial distress, if this knowledge is not applied in financial behavior. The results also show that financial attitude affects financial distress either directly or through financial behavior.